CAUSES OF TRACTOR BREAKDOWNS AND REQUISITE SOLUTIONS A CASE STUDY OF SMALL TRACTOR USE IN RIAU PROVINCE, INDONESIA - Ujang Paman; S. Uchida; S. Inaba; T. Kojima (ASEAN Journal on Science and Technology for Development, 2008)
A survey has been undertaken to look into the causes of tractor breakdowns on field operations and the main constraints associated with repair and maintenance, and to recommend a solution to the problems in Riau Province. The owners of sixty-two small tractors were interviewed, from three regencies chosen of the Province in 2003.  As a result, the working capacity of the tractors was relatively high and the average annual use was relatively low compared to the national average.  Most tractor operators did not have sufficient skill to operate tractors.  The tractor breakdowns resulted from operators’ mistakes, fuel and oil defilement, rough field conditions, poor maintenance, intense use, and factory design.  Inadequate repair shops, a lack of spare parts, and a shortage of mechanics in the local vicinity were the main factors curbing tractor repair. It was also found that inadequate finances led many farmers to ignore tractor maintenance. These suggest that tractor operators should be well trained and tractor-supporting facilities should be provided in rural areas. A mechanical extension officer and credit options should be made available for farmers.